Challenging the antiquity of the Cradle of Humankind, South Africa: Geochronological evidence restricts the age of Eurotomys bolti and Parapapio to less than 2.3 Ma at Waypoint 160, Bolt's Farm. Issue 178 (May 2023) - Edwards, Tara R.; Pickering, Robyn; Mallett, Tom L.; Herries, Andy I.R.
Abstract: Waypoint 160 is a paleocave at Bolt's Farm in the 'Cradle of Humankind, ' South Africa. It is known for the novel murid taxa Eurotomys bolti, argued to be morphologically intermediate between Eurotomys pelomyoides from Langebaanweg (∼5.1 Ma) and the earliest Otomyinae from Makapansgat Limeworks (∼3.0–2.6 Ma). Based on the presence of this specimen, an age of ∼4.5 Ma was inferred for Waypoint 160, making it far older than other Cradle sites. This biochronological age was used to argue that Parapapio and Cercopithecoides fossils from Waypoint 160 were the oldest in the region. Here, we provide a detailed sedimentological context for the in-situ deposits at Waypoint 160. We have identified interior cave deposits, in contrast to other sites at Bolt's Farm. Petrography confirms that one unit (facies D) contains in-situ microfaunal fossils, indicating the likely provenience of the E. bolti specimen. Palaeomagnetic analysis shows four periods of magnetic polarity in the sequence. Using U–Pb ages as chronological pins, we argue that the upper part of the sequence records a polarity change at the end of the Olduvai subChron (1.78 Ma). The lower part of the sequence records a polarity shift from normal to reversed that likely relates to the Feni subChron (2.16–2.12 Ma), based on a basal flowstone U–Pb age of 2.269 ± 0.075 Ma. Together this points to a depositional window of ∼500 ka, with the Parapapio and E. bolti tentatively attributed to the micromammal fossil-bearing layers dating to ∼2.27–2.07 Ma. This has significant implications for other biochronological dates in South Africa, as E. bolti is now less than ∼2.27 Ma, younger than the oldest Otomyinae at Makapansgat Limeworks and thus not ancestral to them. This chronology for Waypoint 160 challenges the presence of older, early to mid-Pliocene deposits >3.20 Ma in the Gauteng portion of the Cradle.